Walther Rathenau : the life of Weimar's fallen statesman - Volkov, Shulamit, 1942- (Yale University Press, 2012)
"This deeply informed biography of Walther Rathenau (1867-1922) tells of a man who--both thoroughly German and unabashedly Jewish--rose to leadership in the German War-Ministry Department during the First World War, and later to the exalted position of foreign minister in the early days of the Weimar Republic. His achievement was unprecedented--no Jew in Germany had ever attained such high political rank. But Rathenau's success was marked by tragedy: within months he was assassinated by right-wing extremists seeking to destroy the newly formed Republic. Drawing on Rathenau's papers and on a depth of knowledge of both modern German and German-Jewish history, Shulamit Volkov creates a finely drawn portrait of this complex man who struggled with his Jewish identity yet treasured his "otherness." Volkov also places Rathenau in the dual context of Imperial and Weimar Germany and of Berlin's financial and intellectual elite. Above all, she illuminates the complex social and psychological milieu of German Jewry in the period before Hitler's rise to power."--Dust jacket flap
Keywords: Rathenau, Walther, -- 1867-1922.; Rathenau, Walther, -- 1867-1922; Germany -- Politics and government -- 1918-1933.; Statesmen -- Germany -- Biography.; Jews -- Germany -- Biography.; Allemagne -- Politique et gouvernement -- 1918-1933.; Hommes d'État -- Allemagne -- Biographies.; Juifs -- Allemagne -- Biographies.; BIOGRAPHY & AUTOBIOGRAPHY -- Historical.; HISTORY -- Europe -- Germany.; BIOGRAPHY & AUTOBIOGRAPHY -- Political.; Jews; Politics and government; Statesmen; Germany; 1918-1933; collective biographies.; Biographies; Biographies.